Sport for Development and Peace in the United Nations: An Empirical Study on the Development of the Role of SDP in the UN in the Context of the Closure of the UNOSDP - Schreiner, Laura; Kastrup, Valerie; Mayer, Jochen (International Studies. Interdisciplinary Political and Cultural Journal, 2024)
In 2017, it was decided that the United Nations Office on Sport for Development and Peace (UNOSDP) is to be closed. This qualitative study aims to analyse the reasons for the closure as well as its effects on Sport for Development and Peace (SDP) in the United Nations. Against the background of the systems theory, we conducted interviews with participants from relevant organisations. It is shown that the way the UNOSDP worked underwent a change and that the new tasks as well as their fulfilment were viewed controversially. Additionally, broader changes in development policy set a new frame for SDP.